2018
DOI: 10.1016/j.maturitas.2018.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Movements of older adults during exergaming interventions that are associated with the Systems Framework for Postural Control: A systematic review

Abstract: One in three older adults fall annually, in part due to impairments in the physiological systems that make up the postural control (PC) system. Exercise, particularly balance training, helps to prevent deterioration and even to improve outcomes in the PC system. Exergaming (exercise-gaming) is interactive computer gaming whereby an individual moves the body in response to onscreen cues in a playful format. Exergaming is an alternative method to standard practice for improving PC outcomes, which has been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 52 publications
4
16
0
Order By: Relevance
“…A possible reason for the difference with previous bicycle training research is that our participants performed standing balance exergames that required participants to stand and perform stepping movements, which directly addresses gait and balance [72]. The exergame we used utilized a changing base of support required to play the games which better meets the specifics for training postural control [73] as compared to sitting on a stationary bicycle. The contrasting findings may also be explained by the spatial versus non-spatial processing demands in combination with the postural modality of the exercises [74].…”
Section: Discussionmentioning
confidence: 99%
“…A possible reason for the difference with previous bicycle training research is that our participants performed standing balance exergames that required participants to stand and perform stepping movements, which directly addresses gait and balance [72]. The exergame we used utilized a changing base of support required to play the games which better meets the specifics for training postural control [73] as compared to sitting on a stationary bicycle. The contrasting findings may also be explained by the spatial versus non-spatial processing demands in combination with the postural modality of the exercises [74].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of difficulty in stepping patterns and frequency were created and different styles of music were chosen to add variety and meet participants' preferences. This approach meets the specifics for training postural control (46) and the postural modality of the exercises in combination with the required spatial processing demands (47) enhances both processing speed and attentional selectivity (48).…”
Section: Exergame-dance Training (Exdt)mentioning
confidence: 93%
“…Exergame studies demonstrated positive benefits for cognition and/or physical functioning in older adults [42, 120–124]; however, the training principle of specificity seems to apply to exergaming. The choice of exergame console [125] and game content used for training [126] influences the areas of (postural) control trained and improved. Which motor and cognitive functions will be or can be improved and triggered through exergaming most likely also depends on the consideration and implementation of training principles (e.g., intensity, frequency, and user-centred).…”
Section: Motor-cognitive Exercisementioning
confidence: 99%